Trends in The Revival of The Uzbek Maqom School - Khayrullaev Bobirjon; Kuziev Islam; Toshev Behruz; Inoyatov Abdurakhman (Researchparks Publishing, 2023)
Today, in independent Uzbekistan, due to the growth of national self-consciousness, the people's interest in their historical past is growing, and the tendencies of the revival of centuries-old traditions are increasing, accompanied at the same time by the processes of reassessment of artistic values. The spiritual significance of Uzbek maqoms is very high: the ancient art of maqoms continues its full-blooded life, forming the basis of the repertoire of many professional and amateur maqom ensembles and performers. Priorities - scientific study, popularization and development (education).